THE ROLE OF STAKEHOLDERS PERCEPTION TOWARDS CHANGE MANAGERS IN PETROLEUM INDUSTRY IN SAUDI ARABIA - Muzammil Ghayas, Dr. Muhammad; Bhutto, Dr. Sana Arz; Mehmood, Dr. Kashif; Jamal, Yasir (The journal of contemporary issues in business and government, 2022)
The aim of this study is to investigate the role of stakeholder's perception towards the change managers in the petroleum industry of Saudi Arabia. Furthermore, the social skills, personal qualities and experience and expertise of the managers as a mediator between the change managers influence and the change management influence is investigated. This study employs a quantitative methodology for which questionnaires were distributed to petroleum industry employees, and a sample of 347 responses were collected for SPSS analysis. The results show that social skills and experience and expertise mediates between change manager influence and change management. The personal qualities show insignificant mediation between change manager influence and change management. This study suggests focus on manager's social skills and experience and expertise which leads to effective change management. This study contributes to the existing body of knowledge in human resource management.